A influ??ncia da cultura nacional no desempenho dos projetos - Pinto, Cl??udia Sofia Frias (2015)
In this study I analyze the influence of national culture in project performance. Specifically, I examine if national culture influences project performance and which cultural dimensions affect project performance. Methodologically, I conducted an empirical study, based in a final sample of 271 project managers and project occurred in 39 different countries. The results showed that cultural dimensions, power distance and future orientation have a negative impact in project performance, and gender egalitarianism has a positive impact in project performance. This study has a theoretical and practical contribution. This study is intended, for one hand, to contribute to the advance of literature in project management and on the other, help project managers preparing for cultural diversity, increasingly common in the projects.